Legal Basis for the Prevention of Transport Terrorism - Davrjon ogli, Rakhimov Mukhammadsodiq (European Journal of Life Safety and Stability (2660-9630), 2022)
This article describes the international and national legal framework for the prevention and suppression of terrorist acts and, in particular acts committed by means of vehicles.